2018
DOI: 10.1007/s41669-018-0097-9
|View full text |Cite
|
Sign up to set email alerts
|

Does Structured Exercise Improve Cognitive Impairment in People with Mild to Moderate Dementia? A Cost-Effectiveness Analysis from a Confirmatory Randomised Controlled Trial: The Dementia and Physical Activity (DAPA) Trial

Abstract: Building on the clinical results of the trial, which showed that the structured exercise programme evaluated does not slow cognitive impairment in people with mild to moderate dementia, this economic evaluation shows that the programme is not cost effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 23 publications
1
23
1
1
Order By: Relevance
“…Although our study showed good cost-effectiveness, a previous study 41) that investigated the cost-effectiveness of an exercise program for older adults who had already developed mild to moderate dementia reported that the program was not cost-effective. Two reasons might be considered for this.…”
Section: Discussioncontrasting
confidence: 55%
“…Although our study showed good cost-effectiveness, a previous study 41) that investigated the cost-effectiveness of an exercise program for older adults who had already developed mild to moderate dementia reported that the program was not cost-effective. Two reasons might be considered for this.…”
Section: Discussioncontrasting
confidence: 55%
“…1). Of the remaining 100 articles, 92 studies were further excluded mainly because of: (1) other publication formats such as conference papers, (2) participants without a formal diagnosis [8,[19][20][21][22], (3) a combination of different interventions [23][24][25][26][27][28], (4) no assessment of target outcome [29][30][31], (5) or institutionalized pwd [32][33][34][35][36]. Consequently, eight publications of seven trials with a total of 1135 participants were included in this review.…”
Section: Included Studiesmentioning
confidence: 99%
“…Иные данные получены в обзоре работ по эффективности психосоциальных мер вмешательства при ведении больных мягкой и умеренной БА. Мета-анализ исследований показал, что сочетание терапии ИХЭ с когнитивным тренингом замедляет прогрессирование деменции и рекомендуется для применения в клинической практике [103].…”
Section: значение когнитивного стиля жизни физических упражнений и пunclassified